Pengalaman Hidup Mistik Santa Teresa Dari Avila Serta Relevansinya Bagi Penghayatan Hidup Imamat Zaman Ini - Lolowang, Ray Legio Angelo (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2022)
Abstrak Pengenalan akan Allah Bapa dan Putera-Nya melalui Roh Kudus dipahami dalam teologi Katolik sebagai hidup mistik. Kehidupan mistik dalam scope ajaran Gereja Katolik itu nyata dalam kesucian hidup para kudus. Salah satunya ialah Santa Teresa dari Avila. Pengalaman hidup Sta. Teresa dari Avila telah banyak memberi sumbangan berarti bagi perkembangan hidup spiritual banyak orang terlebih bagi seorang imam Kristus. Seorang imam sebagai promotor kehidupan spiritual sejatinya berkaca dari pengalaman Sta. Teresa dari Avila ini. Secara eksplisit gambaran tentang hidup saleh, suci dan yang berkenan kepada Allah seperti yang Sta. Teresa dari Avila hidupi itu ditunjukkan dalam berbagai ajaran Gereja. Telaah tentang Teologi Mistik dari sudut pandang Gereja Katolik dalam artikel ini didasarkan pada pengalaman pribadi orang kudus Gereja, Santa Teresa dari Avila bersama dengan Allah dalam hidup doa. Semakin Ia mengenal-Nya dalam kehidupan doa yang mendalam, semakin ia mengalami persatuan cinta mesra dengan Allah. Hidup dan Karyanya menjadi acuan hidup bagi imam di zaman sekarang dalam hidup spiritual dan usaha membangung keakraban yang mesra dengan Allah. Hidup doa dan relasi dengan Allah akan membawa pada keakraban dengan sesama sebagai wujud kesatuan tubuh mistik Kristus. AbstractThe knowledge of God the Father and His Son through the Holy Spirit is understood in Catholic theology as mystical life. The mystical life within the scope of the teachings of the Catholic Church is embodied in the sanctity of the life of the saints. One of them is Saint Teresa of Avila. The life experience of S. Teresa of Avila has made many important contributions to the spiritual development of many people, especially for a priest of Christ. The pastor as a mover of spiritual life actually reflects the experience of S. Teresa from Avila. A clear description of a pious, holy and pleasant life as stated by S. Teresa Avila's life is featured in various Church teachings. The study of mystical theology from the point of view of the Catholic Church in this article is based on the personal experience of the saint of the Church, S. Teresa of Avila with God in the life of prayer. The more she knows Him in a life of deep prayer, the more she experiences a passionate union of love with God. His life and work become a reference for priest this era in their spiritual life and efforts to build intimacy with God. A life of prayer and relationship with God will lead to intimacy with others as a manifestation of the unity of the mystical body of Christ.